Locking down adolescent hunger: COVID-19 and food security in Bangladesh - Seager, Jennifer; Baird, Sarah; Kalow, Jared; Tauseef, Salauddin (Wiley, 2023)
Policy responses to slow the spread of COVID‐19 have increased economic insecurity globally. We use panel data collected immediately before and during the COVID‐19 pandemic with adolescents in Bangladesh to assess the association between COVID‐19‐related restrictions and adolescent hunger. One year into the pandemic, adolescents were three‐fold more likely to report hunger, and households were twice as likely to report cutting back food to adolescents compared to before COVID‐19 restrictions. Vulnerable households experienced larger increases in hunger and reductions in food consumption, with girls more adversely affected than boys. Cash and food aid were unable to mitigate these negative trends.